Strategi Guru dalam Mengoptimalkan Pembelajaran IPAS Kurikulum Merdeka di SDN Kraton 6 - Aurel Dealova; Chelsylia Putri Viantica; Aurel Zahwa Mutiara Dealova; Shelvi Nerisa Arviana; Muhammad Immadudin; Arif Mahya Fanny (STKIP Subang, 2026)
This study aims to describe teachers' strategies in optimizing the implementation of Science and Social Studies (IPAS) learning based on the Merdeka Curriculum in Grade III at SDN Kraton 6. The study employed a descriptive qualitative approach involving the classroom teacher and third-grade students as research subjects. Data were collected through observation, interviews, and documentation. The findings revealed that the teacher implemented various student-centered learning strategies, including group learning, classroom discussions, and motivational approaches through personal interaction and ice-breaking activities. These strategies successfully created an interactive and conducive learning environment and encouraged students' active participation in the learning process. In addition, the teacher conducted assessments covering cognitive, affective, and psychomotor aspects and provided remedial and enrichment activities according to students' learning needs. However, several challenges were identified, including limited instructional time, teachers' administrative workload, suboptimal utilization of technology, and the presence of students who were still less active during learning activities. Overall, the teacher's strategies in optimizing IPAS learning based on the Merdeka Curriculum at SDN Kraton 6 have been implemented effectively and are aligned with student-centered learning principles. Nevertheless, improvements are still needed in time management, technology integration, and strategies for enhancing student motivation.